Macroinvertebrate and diatom indicators of baseline conditions for setting targets in agricultural BMP restoration - Stefanie A. Kroll (Wiley, 2021)
Abstract Recovery trajectories from restoration projects are poorly understood, making it difficult to set restoration targets as part of project planning. As part of the Delaware River Watershed Initiative (DRWI), we collected baseline environmental and biological data at 84 sites in watersheds where agricultural Best Management Practices (BMPs) are being implemented and forested land is being preserved. The objective of this study was to understand which diatom and macroinvertebrate community measures best characterize biological integrity along a gradient of land cover, habitat measures, and water chemistry in order to later set targets for recovery. To this end, we ran separate Redundancy Analysis (RDA) ordinations in which environmental variables constrained (1) community metrics and (2) relative abundance (taxonomic composition) for macroinvertebrates and diatoms. To understand where along the environmental gradient the sites were represented differently by the respective biotic community measures (community metrics and taxonomic composition), the two constrained ordinations were then compared using Procrustes distance. For macroinvertebrate communities, we saw the most agreement in site characterization between the ordinations at intermediate % agricultural land, but disagreement at both high and low % agricultural land. For diatom communities, we saw the most agreement between the site characterizations at high to intermediate % agricultural land, with increasing disagreement associated with increasing % forested land cover. Use of baseline data to set targets for ecosystem recovery requires consideration of which data are most relevant for the site conditions and what amount of change is feasible based on project implementation and effectiveness. A key aspect of choosing endpoints is when the loss of information inherent to metrics makes them less useful for accurately evaluating ecological integrity, especially when looking to capture incremental changes. Based on our findings, we suggest the use of some community metrics and some key taxa to set targets of recovery in biotic communities in agricultural streams, and that these targets be adjusted to best fit the ecological conditions at a given site within a larger data set. Accordingly, monitoring must take place in the context of regional conditions and must be designed to inform target‐setting.